2009
DOI: 10.1111/j.1471-4159.2009.06431.x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal seizures alter the expression of the pannexin and connexin transcriptome

Abstract: Some forms of seizure activity can be stopped by gap junctional (GJ) blockade. Here, we found that GJ blockers attenuate hippocampal seizure activity induced by a novel seizuregenic protocol using Co 2+ . We hypothesized that this activity may occur because of the altered expression of connexin (Cx) and/or pannexin (Panx) mRNAs and protein.We found a 1.5-, 1.4-, and 2-fold increase in Panx1, Panx2, and Cx43 mRNAs, respectively. Significant post-translational modifications of the proteins Cx43 and Panx1 were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 50 publications
6
65
1
Order By: Relevance
“…In Co 2+ -induced epileptiform discharges, Cx43 mRNA and protein are up-regulated, while the mRNA levels of Cx26, Cx30, Cx32, Cx36, Cx40, Cx45, and Cx47 do not change in the hippocampus [79] . In mouse hippocampal slices, 2-to 10-hour exposure to bicuculline induces marked increases in Cx32 mRNA and protein, with no changes in the protein and mRNA levels of Cx26 and Cx43 [80] .…”
Section: Mimetic Peptides As Gap Junction Blockersmentioning
confidence: 99%
See 2 more Smart Citations
“…In Co 2+ -induced epileptiform discharges, Cx43 mRNA and protein are up-regulated, while the mRNA levels of Cx26, Cx30, Cx32, Cx36, Cx40, Cx45, and Cx47 do not change in the hippocampus [79] . In mouse hippocampal slices, 2-to 10-hour exposure to bicuculline induces marked increases in Cx32 mRNA and protein, with no changes in the protein and mRNA levels of Cx26 and Cx43 [80] .…”
Section: Mimetic Peptides As Gap Junction Blockersmentioning
confidence: 99%
“…-induced epileptiform C57BL/6 male mice In the presence of octanol, no ictal or interictal discharges recorded but discharges Whole hippocampus basal rhythmic activity is evident [79] .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon induction of hippocampal seizures, there was a coordinated upregulation of Cx43, Panx1, and Panx2 both at the mRNA and protein level, with changes also reported in the post-translational modifications of Panx1 (glycosylation) and Cx43 (phosphorylation) induced upon seizure induction. 30 Furthermore, ectopic expression of Panx3 in differentiated C2C12 cells has also been recently reported to trigger the expression of Cx43, whereas Panx3 knockdown seemed to downregulate Cx43 expression. 5 In the same study, the increase in gap junction function as measured by intercellular calcium wave propagation was attributed to Panx3 gap junction channels because of channel blockage by carbenoxolone treatment.…”
Section: Cross-talk With Connexin Hemichannelsmentioning
confidence: 99%
“…9 Interestingly, the level of Panx1 glycosylation was reported to change in the male reproductive tract of rats in response to orchidectomy, 22 as well as after induction of hippocampal seizures by Co 2+ treatment in mouse brains. 30 All these phenomena suggests a role for the glycosylation state regulating pannexin function. One additional post-translational modification has been reported for Panx2 in a study where an ∼80 kDa species expressed in neural progenitor cells was found to be sensitive to hydroxylamine suggesting that Panx2 could be palmitoylated.…”
Section: Post-translational Modification Of Pannexinsmentioning
confidence: 99%